Soliloquy in the Novel Crime and Punishment by Fyodor Dostoevsky - Resty Wahyuni; Halimah Tussadiah (English Teaching and Linguistics Journal (ETLiJ), 2022)
There are numerous sorts utterance in drama, one of the sort is soliloquy. Soliloquy is a speech uttered by a character that aims to express feelings or expressions, even messages from a story, in a way that no one knows what he said except the reader or audience. This research were focused on analyzing soliloquy in the novel Crime and Punishment by Fyodor Dostoevsky. The purposes of this research were to find the soliloquy in the novel Crime and Punishment, also, to describe the causes of soliloquy were used in the novel Crime and Punishment by Fyodor Dostoevsky. The researcher applied a descriptive qualitative method. The data was acquired from the novel Crime and Punishment by Fyodor Dostoevsky. The researcher used some theories in research method. Based on the analysis of soliloquy in the novel Crime and Punishment. there were 47 soliloquy that found in the novel Crime and Punishment. The type of soliloquy that found in the novel Crime and Punishment is plain soliloquy. Besides, there two causes that soliloquy were used in the novel Crime and Punishment by Fyodor Dostoevsky, to wit, the reason of the genre, and the reason of the expression feelings. In spite of, a lot of factors that can be the reason of soliloquy were used in the novel, researcher found the strong reason to fyodor to used the soliloquy frequently.